-(1-7x)=4x-13

Simple and best practice solution for -(1-7x)=4x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(1-7x)=4x-13 equation:


Simplifying
-1(1 + -7x) = 4x + -13
(1 * -1 + -7x * -1) = 4x + -13
(-1 + 7x) = 4x + -13

Reorder the terms:
-1 + 7x = -13 + 4x

Solving
-1 + 7x = -13 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-1 + 7x + -4x = -13 + 4x + -4x

Combine like terms: 7x + -4x = 3x
-1 + 3x = -13 + 4x + -4x

Combine like terms: 4x + -4x = 0
-1 + 3x = -13 + 0
-1 + 3x = -13

Add '1' to each side of the equation.
-1 + 1 + 3x = -13 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = -13 + 1
3x = -13 + 1

Combine like terms: -13 + 1 = -12
3x = -12

Divide each side by '3'.
x = -4

Simplifying
x = -4

See similar equations:

| 2x^2-12x-27=0 | | 5=5-4s-7s | | .4x-.03= | | 3x+x+40=180 | | x-20+2-(-7)=9 | | 3b-5+6b=-5 | | 1/6X-5=-11 | | 11-(8-8n)=8 | | (-16)-(-t)=(-45) | | 4(7y-3)= | | 3(2x+1)-5=10 | | 100n+10n=0n+15n | | -1(-m+n+1)= | | 1/5+1/4x=1/3x+5/6 | | -5=6x+4+3x | | 4/7=11/14x-4/7x | | 3(x+5)=3x+5+15 | | 3-10k=5b | | 1608-v=6v | | 11x-3x=-48 | | 0.666m-4=10 | | -1(18a-17b)= | | -.05*-.5= | | H+12-h=28 | | 7+-3(5t+-10)=67 | | -90=-12-2.6x | | 17x+18y+19+20x-12y-9= | | 10x-12x-7y=8 | | 7*k=168 | | z^6/z^9 | | 2(v-1)=4v+4-2(-8v-2) | | 75-9h=20+10h |

Equations solver categories